El simulador Risky Business como herramienta para la toma de decisiones empresariales en los estudiantes de la Universidad Técnica De Cotopaxi, de la Carrera de Ingeniería Comercial, período 2014 - Jácome Constante, Diana Carolina (2015)
This research work was carried out with the need to improve the business skills using a simulator at the Technical University of Cotopaxi, Academic Unit of Administrative and Humanistic Science in the Commercial Engineering Major, detecting as problem that students do not participate in experiences that reinforce the principle of learning doing, focused on skill development. In this study the deductive, analytical method which corresponds to a documentary and field research was used. After an extensive analysis on the use of NTIC’S in Higher Education, we proceeded to the collection of information were surveys and interviews with students and teachers with knowledge of the matter, in order to know if the University counts with adequate laboratory and if students manage some kind of simulator. The result were that students have an incomplete level of the New Technologies of Information and Communication and was not used in Course also unaware on Financial Simulation and lack of technological means that are not used at 100% for the student more competitive. Hence the purpose of implementing a simulator manual Risky Business for understanding the operation. Therefore the proposal of this research will benefit students and faculty of the School of Business and Engineering support in the development of learning skills and competencies, as students can permanently use with teachers to perform actual analysis practices financial resources to making business decisions without difficulty.